Individual, social and structural factors influencing PrEP uptake among cisgender women: a theory-informed elicitation study. Issue 3 (4th March 2022) - Teitelman, Anne M.; Tieu, Hong-Van; Flores, Dalmacio; Bannon, Jacqueline; Brawner, Bridgette M.; Davis, Annet; Gugerty, Paige; Koblin, Beryl
ABSTRACT: The underutilization of pre-exposure prophylaxis (PrEP) among cisgender women in the U.S. limits this population's ability to reduce their risk for HIV infection, especially within the unique individual, social and structural systems they navigate. There is a need to identify the relevant multi-level barriers and facilitators to PrEP use among cisgender women to inform theory-guided efforts that address HIV disparities by race/ethnicity among cisgender women. Guided by the Integrated Behavioral Model and the Behavioral Model of Vulnerble Populations we conducted 41 interviews with PrEP eligible cisgender women in New York City and Philadelphia. Directed content analysis identified 11 modal behavioral beliefs crucial to PrEP uptake, including anticipated negative social consequences, 5 normative beliefs centered on available social supports, and 9 control beliefs such as anticipated barriers such as cost. Awareness and knowledge of PrEP as a biobehavioral HIV prevention method is limited for this sample. Through conventional content analysis we identified interpersonal and structural barriers to PrEP uptake including lack of partner support, transportation, mental health challenges, and challenges in accessing PrEP care. Potential solutions to structural barriers were enumerated along with implications for future intervention work and public health programming.